Spotkanie z Innym (człowiekiem i – niekiedy, być może – z Bogiem) w poezji Stanisława Barańczaka - Fazan, Jarosław (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
This outline touches upon the issue of the (failure of) communication as a challenge to modern poetry about political and anthropological topics. The author is interested in how Stanisław Barańczak’s poetry presents a meeting between people which is, first and foremost, a relationship with otherness describing the identity of an individual and their difference from the others. This relationship is often linked to power and violence that use the language of propaganda as a tool that poetry attempts to deconstruct and discredit. A unique extension of the human–human relationship is a search for a relationship with an entity other than human, which the poetry of the author of Journey in Winter (Podróż zimowa) presents as possible, yet actually unachievable.